Celebrity detox : the fame game - O'Donnell, Rosie (New York, NY : Grand Central Pub., 2007)
"If you live like a famous person, you will pay the price. And it's a high price, and a dangerous game, because fame, the drug can sneak up on you ... until you're so far away from ... 'real, ' that you don't even know you're not 'real' anymore." When O'Donnell's mother was diagnosed with cancer, ten-year-old Rosie believed that if she could become famous, she could buy her mom the miracle cure. Her mother died, but the bond in her mind between stardom and hope survived. This is Rosie's story of the years after she walked away from her top-rated TV show in 2002, and her reasons for going back on the air in 2006. She illuminates not only what it's like to be a celebrity, but also what it's like to be a mother, a daughter, a leader, a friend, a sister, a wife--in short, a human being.
Keywords: O'Donnell, Rosie; Comedians -- United States -- Biography; Motion picture actors and actresses -- United States -- Biography; Television personalities -- United States -- Biography